Development of Kahoot-Based Cognitive Learning Outcome Evaluation for Elementary School Students in Science Learning - Renita, Renita; Suciati, Suciati; Suhartono, Suhartono (Electronic Journal of Education, Social Economics and Technology, 2025)
The integration of technology in education represents a strategic effort to enhance the quality and effectiveness of learning processes. One form of technological innovation in assessment is the use of the Kahoot application as a digital evaluation tool. Learning assessment serves as concrete evidence to measure students’ cognitive development. This study aimed to: (a) develop a valid Kahoot-based assessment product for evaluating cognitive learning outcomes of elementary school students in IPAS (science and social studies) learning; (b) examine the practicality of the Kahoot application as an assessment tool; and (c) analyze its effectiveness in improving students’ cognitive learning outcomes. This research employed a Research and Development (RD) approach using the ADDIE development model. The research subjects were fourth-grade students from SD Negeri 012 Jempang and SD Negeri 010 Jempang. Data were collected through interviews, questionnaires, and tests, and analyzed using descriptive qualitative and descriptive quantitative techniques. The results indicated that the Kahoot-based assessment was highly feasible, with validation scores of 100% from material experts, 92% from media experts, and 88% from language experts. Furthermore, the application was categorized as very practical and demonstrated effectiveness in improving cognitive learning outcomes of fourth-grade students at SDN 010 Jempang, East Kalimantan.